In vitro toxicological prospection of fungicides containing Difenoconazole or Tebuconazole as active ingredients - Trento, Marcus Vinicius; Cesar, Pedro Henrique; Andrade Machado, Gustavo Henrique; Aparecida Braga, Mariana; Silva de Abreu, Tatiane; Andrade-Vieira, Larissa; Marcussi, Silvana (Acta Biológica Paranaense, 2022)
The active ingredients (AI) tebuconazole and difenoconazole (classified as toxic to living organisms and potentially mutagen, carcinogen, or teratogen) are part of the composition of widely used fungicides in crops. In 2016 they were found in irregular quantities by ANVISA in their latest report emitted by the Program of Analysis of Agrochemical Waste in Food. Two commercial fungicides containing the active ingredients tebuconazole and difenoconazole were evaluated in cytogenotoxic assays and on different biological molecules. Both active ingredients altered the clotting time of the plasma, and were procoagulants in the majority of the evaluated doses. The two AI acted on blood thrombi exerting thrombotic action and confirming the observed procoagulant potential. In the proteolysis assay, the AI did not alter the structure of fibrinogen under the conditions evaluated. Tebuconazole and Difenoconazole were also cytotoxic to human erythrocytes, as well as induced phospholipid breakdown, confirming their toxicity on membranes. However, under the conditions evaluated, the AI did not alter significantly the mitochondrial succinate dehydrogenase activity and did not induce DNA fragmentation. Assuming that changes in human cells and molecules have a cumulative effect, the toxic potential of fungicides might be greater when chronic exposure to their active principles occurs.